Sciatic neuropathy following endovascular treatment of a limb vascular malformation - Ney, John P; Shih, William; Landau, Mark E (Journal of Brachial Plexus and Peripheral Nerve Injury, 2006)
Background Endovascular therapy for vascular malformations is one of the treatment options for limb vascular malformations.Case presentation A patient with a vascular malformation of the hip developed ipsilateral leg weakness immediately after endovascular embolization and sclerotherapy. Clinical and electrodiagnostic findings later confirmed an incomplete sciatic neuropathy.Conclusion We propose that endovascular treatment compromised the patient’s sciatic nerve either through direct neurotoxicity of the sclerosing agent or ischemic injury.